Translation Procedures of The Animated Movie “A Stork’s Journey” - Wedriyani, Kadek Ira; Hikmaharyanti , Putu Desi Anggerina (Jurnal Penelitian Mahasiswa Indonesia, 2024)
This study focuses on examining the types of translation procedures in the Indonesian rendition of the animated film "A Stork’s Journey". The research design adopted was descriptive, employing content analysis as the methodology. The process involved an examination of an animated film and its Indonesian translation. Detailed records of dialogues from both versions were methodically compiled, enabling a thorough examination of the source language (SL) and target language (TL) data. In the process of data analysis, dialogues were systematically classified, and the translation methods employed in the film were identified. The translator predominantly employed direct and oblique translation procedures. Examples of direct translation techniques included borrowing, calque, and literal translation, while oblique techniques encompassed transportation, modulation, equivalency, and adaptation.